2016
DOI: 10.1590/0034-7612134163
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for leading indicators on sustainable regional development

Abstract: This research depicts an exploratory initiative focused on treating data to create score and rank indicators of sustainability that can be used to monitor sustainable regional development in metropolitan regions. In order to characterize, classify, and predict the conditions that might lead to the sustainable regional development of cities in a metropolitan area, the study of municipalities in the Baixada Fluminense (region neighboring the city of Rio de Janeiro) was adopted as a reference. The operational ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
5
0
4
Order By: Relevance
“…A região da Ibiapaba depende do equilíbrio na exploração dos recursos, devido à vinculação econômica relacionada à produção agrícola e ao turismo. Caso não haja a manutenção dos ciclos naturais a sustentabilidade regional estará comprometida (REZENDE et al, 2016).…”
Section: Dimensões Ambiental E Ecológicaunclassified
“…A região da Ibiapaba depende do equilíbrio na exploração dos recursos, devido à vinculação econômica relacionada à produção agrícola e ao turismo. Caso não haja a manutenção dos ciclos naturais a sustentabilidade regional estará comprometida (REZENDE et al, 2016).…”
Section: Dimensões Ambiental E Ecológicaunclassified
“…Методология исследования. Был проведен анализ содержания схем теплоснабжения семи населенных пунктов России [19][20][21][22][23][24][25] и нормативного документа, его регламентирующего (ПП РФ от 22.02.2012 №154).…”
Section: Level Of Comfort Has Been Analyzed From the Point Of View Ofunclassified
“…Результаты анализа утвержденных схем теплоснабжения. Все рассмотренные схемы [19][20][21][22][23][24][25] имеют одинаковые недостатки:…”
Section: Level Of Comfort Has Been Analyzed From the Point Of View Ofunclassified
“…J. Rezende, M. Sinay, in particular, developed an array of indicators most relevant to sustainable development goals based on direct interpretation of these goals and tested it in Brazil. As a result, it was found that many economically developed territories have a low degree of stability [11].…”
Section: Introductionmentioning
confidence: 99%